Pengukuran Kinerja Pemerintah Daerah: Kontribusi Sektor Pariwisata terhadap Pendapatan Asli Daerah pada Kabupaten Manggarai Barat - Odilia Fitriyani Harti; Maria Odriana Veronica Moi; Antonius Yohanes William Timuneno (AKSIOMA : Jurnal Manajemen, 2024)
This study aims to measure the performance of local governments, one of which is through the contribution of tourism sector revenues consisting of local taxes and local levies. Local taxes in the tourism sector consist of hotel tax, restaurant tax and entertainment tax. Local levies in the tourism sector consist of levies for recreational areas and levies for tourist attractions. Data were collected from 2017-2021 and analyzed using the degree of contribution formula which is classified based on the level of contribution. The results showed that the contribution of tourism sector local revenue to PAD of West Manggarai Regency in 2017-2021 averaged 25.73% with a moderate category. When viewed from each source of tourism sector revenue, both local taxes and local levies are in the very poor category.